2020
DOI: 10.1103/physrevlett.125.027001
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Dome in Nd1xSrxNiO2 Infinite Layer Films

Abstract: We report the phase diagram of Nd1-xSrxNiO2 infinite layer thin films grown on SrTiO3. A superconducting dome spanning 0.125 < x < 0.25 is found, remarkably similar to cuprates, albeit over a narrower doping window. However, while cuprate superconductivity is bounded by an insulator for underdoping and a metal for overdoping, here we observe weakly insulating behavior on either side of the dome. Furthermore, the normal state Hall coefficient is always small and proximate to a continuous zero crossing in doping… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
211
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(257 citation statements)
references
References 54 publications
34
211
0
Order By: Relevance
“…However, both Ni and Nd sites typically display significant magnetic moments with considerable evidence of magnetic fluctuations or short-range order [31,46]. Moreover, the undoped nickelates are not ordinary metals, but weak insulators [8,10]. In our previous SCANbased studies of other correlated materials, we found many low-energy magnetic phases indicative of prominent magnetic fluctuations [36,37,43].…”
Section: Comparisons With Cupratesmentioning
confidence: 81%
See 2 more Smart Citations
“…However, both Ni and Nd sites typically display significant magnetic moments with considerable evidence of magnetic fluctuations or short-range order [31,46]. Moreover, the undoped nickelates are not ordinary metals, but weak insulators [8,10]. In our previous SCANbased studies of other correlated materials, we found many low-energy magnetic phases indicative of prominent magnetic fluctuations [36,37,43].…”
Section: Comparisons With Cupratesmentioning
confidence: 81%
“…Recently, superconductivity in the hole-doped infinitelayer nickelate NdNiO 2 at 9∼15K has been reported in thin film samples grown on SrTiO 3 [7][8][9][10], although superconductivity in bulk NdNiO 2 has not been observed [11]. These results [7] have reinvigorated interest in searching for the microscopic mechanism of HTSC and stimulated many new open questions [10][11][12][13][14][15][16][17][18][19][20]. Notably, superconductivity is present both in hole-doped NdNiO 2 [7] and PrNiO 2 [21], but absent in LaNiO 2 [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another controversial issue for NdNiO 2 is to which orbitals the doped holes go (d 9 L vs d 8 , where L denotes a hole in a ligand oxygen). In the case of the cuprates (charge-transfer insulator), the holes are doped into the oxygen 2p orbitals.…”
Section: Materials: D 9 Nickelatesmentioning
confidence: 99%
“…The discovery of superconductivity in doped nickel oxides Nd 0.8 Sr 0.2 NiO 2 [1,2] has attracted intensive interest in both experiment [3][4][5][6][7][8][9][10][11][12][13] and theory [3, because the nickelate might be an analog of the well-known high-T c superconductor, cuprates. Recently, the doping dependence has been explored both theoretically [37] and experimentally [8,9] and the presence of the superconducting dome has been confirmed [8,9]. The maximum superconducting transition temperature T c is about 15 K, not very high compared to that of the high-T c cuprates.…”
Section: Introductionmentioning
confidence: 99%